International marketing : n - Fletcher, Richard, 1940- 4 0 16; Brown, Linden; 5 (Frenchs Forest, N.S.W. : Pearson Education Australia)
u
Includes bibliographical references and index.
Keywords: 2 -- 0; 6; International business enterprises.;Export marketing;Export marketing -- Asia.;Pacific Area; 20; 2